The Effect Of Taxpayer Compliance On The Realization Of Parking Tax Revenue In Sumedang Regency - Ai Nunung Sri Haryati Haryati; Erpi Rahman; Lisna Lisnawati (LPPM Universitas Sebelas April, 2021)
The main problem in this research is the not optimal Parking Tax. Parking tax is a type of regional tax that is quite potential as a source of revenue for the City of Sumedang. The purpose of this study was to determine the effect of taxpayer compliance on the realization of parking tax revenues in Sumedang Regency. This research method uses descriptive survey method with a quantitative approach. The population in this study was all parking taxpayers in Sumedang Regency by taking saturated sampling techniques. The data source is a type of primary data with a questionnaire as an instrument given to 73 respondents with a Likert scale of 1 to 5. The statistical method used is a simple linear regression analysis. This study shows there is a strong correlation between taxpayer compliance with the realization of parking tax revenues by 76.1%. The coefficient of determination of the remaining 57.9% of 42.1% is influenced by other factors not discussed in this study. The results of the regression analysis are expressed by the equation Y = 13,995 + 0,692x with a tcount of 9,884> a table of 1,66660 with the hypothesis of this study accepted.